A new solvate of clonixin and a comparison of the two clonixin solvates. Issue 40 (16th July 2021) - Zhoujin, Yunping; Zhang, Mingtao; Parkin, Sean; Li, Tonglei; Yu, Faquan; Long, Sihui
Abstract : A new solvate of clonixin (CLX ), a dimethylacetamide (DMA) solvate, has been obtained by crystal growth in DMA. Abstract : A new solvate of clonixin (CLX ), a dimethylacetamide (DMA) solvate, has been obtained by crystal growth in DMA. The new form was characterized by NMR, single-crystal X-ray diffraction, and PXRD. The crystal structure is stabilized by a strong hydrogen bond between the carboxylic acid OH of CLX and the DMA carbonyl, the strength of which is on par with those of the four solvent-free forms of CLX and the DMF solvate. These previously known forms are based on either the acid–acid homosynthon or the acid–pyridine heterosynthon, depending on the dihedral angle between the two aromatic rings of CLX, or the heterodimer between CLX and DMF. The new solvate loses DMA to convert into form I of CLX, as confirmed by differential scanning calorimetry (DSC) and powder X-ray diffraction (PXRD), similar to how the DMF solvate does. A comparison of the two solvates was carried out and theoretical studies were performed to shed light on the conformational difference between the two CLX molecules in the two solvates and the packing differences between them. The insight gained on this solvatomorphic system could aid the design of new solvates and cocrystals of CLX .